A monitoração ambiental no setor de informática em Minas: um mapeamento de segmentos e fontes - Ana Claudia Piedade Silveira (1999)
Environmental scanning, conceived as a process involving the search and use of external information as an input to corporate planning and strategic management, allows organizations to monitor events and trends which are relevant to their future courses of action. This exploratory study, conducted in the computer science sector of the State of Minas Gerias, Brazil, describes aspects of the external organizational environment and tries to answer the following questions: a) which are the most relevant external information form the perspectives of the companies managers; b) which sectors of the environment need to be monitored and c) which information sources are used in the scanning process. The data form the 52 companies that participated of the study were obtainde through the Internet. Results obtained for previous research on environmental scanning are confirmed in this study, such as the managers' preferences for personal sources information, their emphasis on specialized serial publications, as well as the importance attributec to the market and technological sectors of their firm's enviroment. This dissertation also presents suggestions for future research, believed to be able to contribute to the knowledge of the environmental scanning process, especially in Brazilian companies.